A Novel Fluorescent Aptasensor Based on Dual-labeled DNA Nanostructure for Simultaneous Detection of Ochratoxin A and Aflatoxin B1 - Zhao, Luyang; Liang, Xiujun; Liu, Yong; Wei, Min; Jin, Huali (Journal of fluorescence, 2023)
Based on DNA strand replacement reaction and aptamer-specific recognition, a simple dual-labeled DNA nanostructure is designed for the simultaneous detection of Ochratoxin A (OTA) and aflatoxin B1 (AFB 1 ). C1 is labeled with Cy3 and Cy5, while C2 and C3 are labeled with BHQ2. The fluorescence intensity of DNA nanostructure composed of C1, C2 and C3 is weak because of fluorescence resonance energy transfer. When OTA Aptamer (OTA-Apt) and AFB1 Aptamer (AFB 1 -Apt) are added to the homogeneous system at the same time, C1 can be replaced with the help of toehold strand displacement, resulting in fluorescence enhancement. In the presence of both OTA and AFB 1 , the toehold strand displacement reaction is inhibited due to preferential binding between the target and their corresponding aptamers. The limit of detection of OTA was 0.007 ng/mL and that of AFB 1 was 0.03 ng/mL. The recoveries of OTA and AFB 1 were 96%-101% and 97%-101% in the corn sample, and 99%-101% and 92%-106% in the wine sample. Compared with other sensors, the preparation of this aptasensor needs simpler experimental steps and a shorter total-preparing time, confirming the convenient, rapid, and time-saving operation process.